Exploring the effect of friction stir welding parameters on the strength of AA2024 and A356-T6 aluminum alloys - Ibrahim Sabry (Journal of Alloys and Metallurgical Systems)
The amalgamation of AA2024 and AA356-T3 in general engineering applications can be advantageous for structures necessitating both elevated strength and corrosion resistance. This is particularly pertinent in manufacturing, where lightweight properties and robustness are crucial, as seen in high-performance industrial equipment. Nevertheless, conventional fusion welding of these aluminium alloys poses significant challenges. This work focuses on examining the mechanical and microstructure characteristics of Alloys made of high-strength aluminium, AA2024, and A356-T6, using the Friction Stir Welding (FSW) process. The investigation evaluated the impacts of key parameters such as rotational speed (RS) ranging from 1000 to 2000 rpm, travel speed (TS) from 10 to 15 mm/min, and tilt angle (1°–2°) on ultimate tensile strength (UTS) tool wear (TW), temperature distribution(T), residual stress (RS) and hardness (HV). The experimental procedure was conducted using Response Surface Methodology (RSM), while SEM was utilized to analyze the fractured surface morphology. According to the results, the highest factor of mechanical properties was obtained for welds made using dissimilar aluminium alloys AA2024 and AA356-T3 with a constant tilt angle of 1.54°, traverse speed of 10 mm/min, and rotational speed of 2000 rpm. The highest tensile strength, hardness, temperature, and residual stress of 381 MPa,114 HVN, 504 C°, and 76.30 MPa respectively, were noted for the weld zone. However, The lowest tool wear of 0.13595 at a constant tilt angle of 1.54°, traverse speed of 15 mm/min, and rotational speed of 1000 rpm.